The Bioclimatic map of Southern Vietnam for tourism development - Van, Nguyen Khanh; Oanh, Hoang Thi Kieu; Vu, Vuong Van; Hien, Le Thi Thuy (Vietnam Journal of Earth Sciences, 2019)
Although research and evaluation of climate conditions for tourism development are a pressing issue, in Vietnam in general and in the Southern region in particular, these studies are still limited. Based on climatological parameters (T-annual temperature, R-rainfall and N-rainy days) with their levels of classification representing the bioclimatic impact on tourism, the bioclimatic classification map of Southern Vietnam is built at the scale of 1:250,000. Base on the calculated data from 20 meteorological stations of Southern Vietnam in many years (1981-2015, 12 suitable bioclimatic units are established. It is a necessary scientific background to organize territory for tourism in Southern Vietnam. With plentiful bioclimatic resources, one can organize many types of tourism in Southern Vietnam. The result of classification and bioclimatic map for tourism is an important and necessary sciential basis which help the orientation of development and tourism territory organization of the governments.